2020
DOI: 10.26434/chemrxiv.13083887.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polysulfide Anions as Visible Light Photoredox Catalysts for Aryl Cross-Couplings

Abstract: Herein, we disclose the use of polysulfide anions as visible light photoredox catalysts for aryl cross-coupling reactions. The reaction design enables single-electron-reduction of aryl halides upon photo-excitation of tetrasulfide dianions (S<sub>4</sub><sup>2–</sup>). The resulting aryl radicals are engaged in (hetero)biaryl cross-coupling, borylation, and hydrogenation in a redox catalytic regime involving S<sub>4</sub><sup>•–</sup>/S<sub>4</sub><… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Satisfyingly, this catalytic system featured broad substrate scope and good functional group compatibility under the optimized reaction conditions (Table 1). Isocyanides substituted with electron-neutral (3, 4) and electron-donating (5) and electron-groups (6) all gave good to excellent yields. A variety of primary, secondary and even tertiary RAEs were all amenable substrates to deliver the corresponding decarboxylative alkylation products in moderate to excellent yields (51% -98%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfyingly, this catalytic system featured broad substrate scope and good functional group compatibility under the optimized reaction conditions (Table 1). Isocyanides substituted with electron-neutral (3, 4) and electron-donating (5) and electron-groups (6) all gave good to excellent yields. A variety of primary, secondary and even tertiary RAEs were all amenable substrates to deliver the corresponding decarboxylative alkylation products in moderate to excellent yields (51% -98%).…”
Section: Resultsmentioning
confidence: 99%
“…Almost every atom (except inert elements) can bond with sulphur atoms, and its valence state can vary from -2 to 6 [5] . The excellent electron-transfer ability and radical properties of sulphur-containing backbones make them ideal candidates for catalysis [6] , particularly in the photoredox pathway [7] . To date, numerous sulphur-containing photosensitizers have been synthesized and employed in visible-light-induced transformations, such as disodium benzophenondisulphonate (BPSS) [8] , thiazine dyes [9] , thiophene derivatives [10] and N-phenylphenothiazine (PTH) [11] .…”
Section: Introductionmentioning
confidence: 99%
“…49−54 Despite their wellexplored photophysical properties, 49,50,53 their use as photocatalysts for chemical reactions has been reported only recently by Chiba and co-workers. 55,56 They showed that polysulfide anions possess a high reduction power after visible-light excitation, capable of single-electron reduction of aryl halides to generate synthetically valuable aryl radicals. The resulting aryl radicals were exploited in aryl−aryl cross-coupling, borylation, and hydrogenation reactions.…”
Section: Light-induced Thiolate Catalysis Enabledmentioning
confidence: 99%
“…Chiba recently disclosed that these polysulfide anions could serve as visiblelight photoredox catalysts to promote a series of aryl crosscoupling reactions. 44 For example, a heterobiaryl crosscoupling reaction between 4′-bromoacetophenone (10) and N-methylpyrrole (80) was promoted by a catalytic amount of K 2 S x in DMSO under irradiation with visible light (440 nm), affording biaryl 81 in good yield within 1.5 h (Scheme 11). The process is proposed to be initiated by SET reduction of aryl bromide 10 by photoexcited S 4 2− to form the radical anion of aryl bromide 82, which subsequently undergoes C−Br bond mesolysis to form aryl radical 83.…”
Section: ■ Photoinduced Molecularmentioning
confidence: 99%